A survey on the potential contribution of Reunion Island dye plant species diversity to the market demand for bioactive plant-based dyes and pigments - Mahery Andriamanantena; Shamsia Pithon; Manon Dijoux; Marine Hoareau; Christian Fontaine; Johnny Ferrard; Christophe Lavergne; Thomas Petit; Yanis Caro (Journal of Ethnobiology and Ethnomedicine, 2023)
Abstract Background Proven toxicity and environmental burdens caused by artificial dyes have motivated dyeing industries to turn to natural alternatives. Plant-based dyestuffs are an interesting group of alternative crops. Reunion Island located in the Indian Ocean is the only European region in the southern hemisphere. It has a great number of assets to find new molecules in the abundant plant biodiversity. However, the dye-producing plants diversity in this island had not been documented to date. Methodology The assessment of the Reunion Island’s plant biodiversity through the “PLANTIN” project allowed us to establish here the first ethnobotanical inventory of plants growing on Reunion Island which may have promising properties as a new alternative source of dyes or colorants for the industries. First, an ethnobotanical survey focused on the uses of plants traditionally used in dyeing was conducted on local stakeholders. Then, the importance of different criteria (e.g., endemicity, accessibility and cultivability, plant organs used for the extraction, industrial interests of the species, etc.) has been considered to establish a classification method of the species, to finally select the most interesting plants which have been further harvested and investigated for their coloring property and dyeing application on natural fibers. Results The results showed that local people have accumulated traditional knowledge of dyeing plants, but that this approach had been discontinued in Reunion. The uses of 194 plant species potentially rich in dyes or pigments, belonging to 72 different families, with diverse botanical status (endemic, native, introduced or alien-invasive species) have been recorded. Then, 43 species were harvested and their coloring property were investigated. It demonstrated that dyes extracted from promising species, e.g., Terminalia bentzoe, Weinmannia tinctoria, Thespesia populnea, Erythroxylum laurifolium, Morinda citrifolia, Leea guinensis, Ochrosia borbonica, Danais fragrans, Terminalia cattapa, Casuarina equisetifolia, and Coccoloba uvifera, amongst others, could be used as new textile dyes. Their efficacy in the wool and cotton dyeing has been successfully demonstrated here. Conclusion These plant-based dyestuffs showed promising coloring properties with different shades that could meet industrial application requirement. It's an area that could promote local cultural inheritance, create opportunity for business and farmers, and that can make a significant contribution to preserving endangered native species by supporting reforestation schemes. Additional researches are in progress to evaluate the safety of these plant-based colored extracts, their chemical composition and biological activities.